EEG pattern of human calmness during listening to Al-Quran recitation and soft instrumental music - Rahim, A. A. A.; Fuad, N.; Marwan, M. E.; Norazlin, Norazlin (Penerbit UTHM, 2022)
Emotions is a really importance and powerful in human life this is because it can affect the brain which is the most importance organ in human organic system. Good emotion will gives a good effect towards the brain and human while the bad emotion will be vice versa from the good emotion. This is the reasons why emotion needs to manage wisely. Calmness is the one thing that people always seek off after having a hard time or stress. Music has a great effect towards human mind and body. It has proven that listening to music increase the alpha wave level associated to the increase of relaxation. Music is one of therapy that beneficial the people who experiencing depression, stress or anxiety. This research used alQuran recitation of Surah al-Shua’ara and soft instrumental music as the material to simulate the brain to generate the calmness. There are 10 subject were recorded the EEG signal during listening to al-Quran recitation and soft instrumental music by using Emotiv Insight equipment. The raw data of EEG will undergo analysing process by using SPSS software to test the accurately of the data. The objective of this research is to compare the calmness between the Al-Quran recitation and soft instrumental music. As the result, it is found that most of the subjects were calm during listening to al-Quran recitation compared to the soft instrumental music, but still the soft instrumental music gives calmness towards the listener this is because alpha wave level is low during listening to them compared to beta wave level. In conclusion, al-Quran recitation gives calmness towards the listener compared to the soft instrumental music.